An Approach to the Measurement, Analysis, and Prediction of Brand Equity and Its Sources - Srinivasan, V.; Park, Chan Su; Chang, Dae Ryun (Management Science, 2005)
The authors propose a new approach for measuring, analyzing, and predicting a brand’s equity in a product market. Brand equity is defined as the incremental contribution ($) per year obtained by the brand in comparison to the underlying product (or service) with no brand-building efforts. The incremental contribution is driven by the individual customer’s incremental choice probability for the brand in comparison to his choice probability for the underlying product with no brand-building efforts. The approach takes into account three sources of brand equity—brand awareness, attribute perception biases, and nonattribute preference—and reveals how much each of the three sources contributes to brand equity. This is done by taking into account not only the direct effects of these three sources on choice probabilities, but also the indirect effects through enhancing the brand’s availability. The method provides what-if analysis capabilities to predict the likely impacts of alternative strategies to enhance a brand’s equity. The survey-based results from applying the method to the digital cellular phone market in Korea show that the proposed approach has good face validity and convergent validity, with brand awareness playing the largest role, followed by nonattribute preference.